Special issue human rights : new possibilities/new problems - Sarat, Austin (Studies in law, politics, and society ;, 2011)
Volume 56 of Studies in Law, Politics, and Society presents the latest scholarship on human rights. The work contained in this volume examines both the theoretical dimensions and dilemmas of human rights in the modern world and particular cases in which the problems and possibilities of human rights are examined. Taken together the contributions point to a need for more searching examination of the way human rights work and highlight the contribution of human rights to the advancement of claims for justice. Studies in Law, Politics, and Society is a leading socio-legal publication that truly embraces innovative, theoretically informed, interdisciplinary legal scholarship.